2018
DOI: 10.1056/nejmoa1703327
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative Autologous Stem-Cell Transplantation for Severe Scleroderma

Abstract: BACKGROUND Despite current therapies, diffuse cutaneous systemic sclerosis (scleroderma) often has a devastating outcome. We compared myeloablative CD34+ selected autologous hematopoietic stem-cell transplantation with immunosuppression by means of 12 monthly infusions of cyclophosphamide in patients with scleroderma. METHODS We randomly assigned adults (18 to 69 years of age) with severe scleroderma to undergo myeloablative autologous stem-cell transplantation (36 participants) or to receive cyclophosphamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
384
1
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 471 publications
(458 citation statements)
references
References 39 publications
(38 reference statements)
9
384
1
24
Order By: Relevance
“…According to the Worldwide Network for Blood and Marrow Transplantation (WBMT), one million HSCTs had been performed by the end of 2012 [4]. In addition to conventional uses of HSCT for the treatment of hematologic malignancies, clinical uses have expanded in recent years to include treatment of severe scleroderma [5], diabetes [6], metabolic disorders [7], and even delivery of gene therapy [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…According to the Worldwide Network for Blood and Marrow Transplantation (WBMT), one million HSCTs had been performed by the end of 2012 [4]. In addition to conventional uses of HSCT for the treatment of hematologic malignancies, clinical uses have expanded in recent years to include treatment of severe scleroderma [5], diabetes [6], metabolic disorders [7], and even delivery of gene therapy [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…25 The eligibility criteria and characteristics of patients enrolled were notably similar among the three trials (Table 1) All three trials demonstrated a benefit in the AHCT arm with respect to their primary endpoints (clinical improvement in ASSIST, event-free survival in ASTIS trial and change in global rank composite score in SCOT trial). Also, patients on the AHCT arm had better overall survival and a lower rate of disease progression.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…A subsequent systematic review and meta-analysis included three randomized trials (including SCOT trial) and one comparative observational study. 17, 2325, 27 The control arm was monthly cyclophosphamide in all three trials and the majority of patients in the observational study. Compared to controls, patients receiving AHCT experienced lower all-cause mortality (risk ratio [RR] 0.50, [95% confidence intervals, 0.33–0.75] P=0.0007), and improved skin thickness, forced vital capacity, total lung capacity, and quality of life.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…For example, in patients with systemic sclerosis, autologous HSCT was found to be associated with stabilization of pulmonary hypertension in affected patients [18]. Additionally, a 5-year post-transplant follow-up study of this same patient cohort demonstrated a trend towards improved lung function parameters, such as the diffusing capacity of lung for carbon monoxide (DLCO) [19], while a more recent clinical trial showed that, in patients with scleroderma, stem cell transplantation can prevent the development of pulmonary hypertension [20]. Similar disease remission following HSCT has been noted in patients with pulmonary hypertension secondary to systemic lupus erythematosus [21,22].…”
Section: Pulmonary Hypertension and Myeloid Cell Disordersmentioning
confidence: 99%